Sex differences in pediatric sepsis—a systematic review protocol - Uchenna Kennedy; Juliette Moulin; Luregn J. Schlapbach; Kusum Menon; Jan Hau Lee; Ulrike Held (Systematic Reviews, 2024)
Abstract Background Pediatric sepsis remains a leading cause of childhood morbidity and mortality worldwide. Despite advancements in modern medicine, it accounts for more than 3 million childhood deaths per year. Multiple studies have emphasized that sex and gender have an impact on the treatment and outcome of various diseases. Adult studies have revealed sex differences in pathophysiological responses to septic shock, as well as a possible protective effect of estrogens on critical illness. Sex-specific maturational and developmental differences in host immunology have been previously demonstrated for neonatal and pediatric age groups. At present, there are no studies assessing the impact of sex on outcomes of children with sepsis. Methods The goal of this study is to assess sex-specific differences in childhood sepsis survival outcomes. We will systematically assess associations of sex and gender with outcomes in pediatric sepsis in the literature by performing a systematic search of MEDLINE and Embase databases. We will include all English language randomized trials and cohort studies. The study population will include children > 37 weeks gestational age and < 18 years of age. Exposure will be sepsis, severe sepsis, and septic shock and the main comparison will be between male and female sex. The primary outcome will be hospital mortality. Secondary outcomes will be the pediatric intensive care unit and hospital length of stay. Discussion Results from this review are expected to provide important information on the association of sex with the outcomes of pediatric sepsis. If an association is noted, this study may serve as a foundation for further research evaluating the pathophysiological aspects as well as potential socioeconomic factors responsible for the clinically detected sex differences. Systematic review registration PROSPERO CRD42022315753.